Parametric and algebraic description of a parabola

Geometry Level 4

Consider the parabola defined parametrically in the x y xy plane by

r ( t ) = C + f 1 t + f 2 t 2 \mathbf{r}(t) = \mathbf{C} + \mathbf{f_1} t + \mathbf{f_2} t^2

The vectors f 1 , f 2 \mathbf{f_1} , \mathbf{f_2} are a pair of linearly independent vectors in R 2 \mathbb{R}^2 .

Suppose that C = ( 5 , 7 ) \mathbf{C} = (5, 7) , f 1 = ( 3 , 1 ) \mathbf{f_1} = (3, 1) and f 2 = ( 1 , 2 ) \mathbf{f_2} = (-1, 2) , then in a suitable coordinate frame V x y Vx'y' the parabola algebraic equation can be expressed as

y = a x 2 y' = a {x'}^2

with a > 0 a \gt 0 , where the origin of the V x y V x' y' coordinate frame is at the vertex V ( x 0 , y 0 ) V (x_0, y_0) of the parabola. If θ 0 \theta_0 is the angle (in radians) that the x x' axis makes with the x x axis, then find

a + x 0 + y 0 + θ 0 a + x_0 + y_0 + \theta_0 .

Note: Coordinate frame V x y V x' y' is just a shifted and rotated frame with respect to the original O x y O x y frame.


The answer is 13.1.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

The vertex of the parabola r ( t ) = C + f 1 t + f 2 t 2 \vec{r}\left( t \right)=\vec{C}+{{\vec{f}}_{1}}t+{{\vec{f}}_{2}}{{t}^{2}} is given by r ( t 0 ) = C + f 1 t 0 + f 2 t 0 2 \vec{r}\left( {{t}_{0}} \right)=\vec{C}+{{\vec{f}}_{1}}{{t}_{0}}+{{\vec{f}}_{2}}{{t}_{0}}^{2} , where t 0 = f 1 f 2 2 f 2 2 {{t}_{0}}=-\frac{{{{\vec{f}}}_{1}}\cdot {{{\vec{f}}}_{2}}}{2{{{\vec{f}}}_{2}}^{2}} (see here ).

Using C = ( 5 , 7 ) \vec{C}=\left( 5,7 \right) , f 1 = ( 3 , 1 ) {{\vec{f}}_{1}}=\left( 3,1 \right) and f 2 = ( 1 , 2 ) {{\vec{f}}_{2}}=\left( -1,2 \right) we get t 0 = 1 10 {{t}_{0}}=\dfrac{1}{10} , thus, the vertex is r ( t 0 ) = ( 5.29 , 7.12 ) \vec{r}\left( {{t}_{0}} \right)=\left( 5.29,\ 7.12 \right) .

Furthermore, the focal length of the parabola is given by f = f 1 2 f 1 2 ( f 1 f 2 ) 2 4 f 2 3 = 49 20 5 f=\dfrac{{{{\vec{f}}}_{1}}^{2}{{{\vec{f}}}_{1}}^{2}-{{\left( {{{\vec{f}}}_{1}}\cdot {{{\vec{f}}}_{2}} \right)}^{2}}}{4{{\left| {{{\vec{f}}}_{2}} \right|}^{3}}}=\dfrac{49}{20\sqrt{5}} .

In the form y = a x 2 {y}'=a{{{x}'}^{2}} , a = 1 4 f a = 5 5 49 . a=\dfrac{1}{4f}\Rightarrow a=\dfrac{5\sqrt{5}}{49}.

Because f 2 {{\vec{f}}_{2}} is parallel to the axis of the parabola, the angle θ 0 {{\theta }_{0}} is equal to the angle that f 2 {{\vec{f}}_{2}} makes with j = ( 0 , 1 ) \vec{j}=\left( 0,1 \right) .

Hence, θ 0 = cos 1 ( f 2 j f j ) = cos 1 ( 2 5 ) {{\theta }_{0}}={{\cos }^{-1}}\left( \frac{{{{\vec{f}}}_{2}}\cdot \vec{j}}{\left| {\vec{f}} \right|\left| {\vec{j}} \right|} \right)={{\cos }^{-1}}\left( \frac{2}{\sqrt{5}} \right) .

For the answer, a + x 0 + y 0 + θ 0 = 5 5 49 + 5.29 + 7.12 + cos 1 ( 2 5 ) 13.1 . a+{{x}_{0}}+{{y}_{0}}+{{\theta }_{0}}=\dfrac{5\sqrt{5}}{49}+5.29+7.12+{{\cos }^{-1}}\left( \frac{2}{\sqrt{5}} \right)\approx \boxed{13.1}.

Great solution. Great animation. If you don't mind me asking, what software did you use to generate the animation ?

Hosam Hajjir - 11 months ago

Thank you, I am glad you liked it. For the animation, at first I used Geogebra and clicked "Animation On" for the slider "t". Then I captured the moving image as an MP4 file with Camtasia, which is a Screen Recorder and Video Editor. Finally, I converted it to a GIF file using an online free converter that can be found here . It is not that much complicated as it sounds :)

Thanos Petropoulos - 11 months ago
David Vreken
Jul 13, 2020

With C = ( 5 , 7 ) \mathbf{C} = (5, 7) , f 1 = ( 3 , 1 ) \mathbf{f_1} = (3, 1) and f 2 = ( 1 , 2 ) \mathbf{f_2} = (-1, 2) , we have parametric equations:

x = 5 + 3 t t 2 x = 5 + 3t - t^2

y = 7 + t + 2 t 2 y = 7 + t + 2t^2

With a little bit of rearranging, we can eliminate t t and obtain:

4 x 2 + 4 x y + y 2 61 x 55 y + 401 = 0 4x^2 + 4xy + y^2 - 61x - 55y + 401 = 0

a conic where A = 4 A = 4 , B = 4 B = 4 , C = 1 C = 1 , D = 61 D = -61 , E = 55 E = -55 , and F = 401 F = 401 , and is rotated θ \theta , where cot 2 θ = A C B = 4 1 4 = 3 4 \cot 2\theta = \frac{A - C}{B} = \frac{4 - 1}{4} = \frac{3}{4} . Using some trig identities, this means that:

sin θ = 5 5 \sin \theta = \frac{\sqrt{5}}{5}

cos θ = 2 5 5 \cos \theta = \frac{2\sqrt{5}}{5}

and applying the tranformation rotation :

A = A cos 2 θ + B sin θ cos θ + C sin 2 θ = 5 A' = A \cos^2 \theta + B \sin \theta \cos \theta + C \sin^2 \theta = 5

B = 2 ( C A ) sin θ cos θ + B ( cos 2 θ sin 2 θ ) = 0 B' = 2(C - A) \sin \theta \cos \theta + B (\cos ^{2} \theta - \sin ^{2} \theta) = 0

C = A sin 2 θ B sin θ cos θ + C cos 2 θ = 0 C' = A \sin^2 \theta - B \sin \theta \cos \theta + C \cos^2 \theta = 0

D = D cos θ + E sin θ = 177 5 5 D' = D \cos \theta + E \sin \theta = -\frac{177\sqrt{5}}{5}

E = D sin θ + E cos θ = 49 5 5 E' = -D \sin \theta + E \cos \theta = -\frac{49\sqrt{5}}{5}

F = F = 401 F' = F = 401

so that a new graph with the same scale is:

5 x 2 177 5 5 x 49 5 5 y + 401 = 0 5x'^2 - \frac{177\sqrt{5}}{5}x' - \frac{49\sqrt{5}}{5}y' + 401 = 0

which rearranges to:

y = 5 5 49 ( x 177 5 50 ) 2 + 179 5 100 y' = \frac{5\sqrt{5}}{49}(x' - \frac{177\sqrt{5}}{50})^2 + \frac{179\sqrt{5}}{100}

so that:

a = 5 5 49 a = \frac{5\sqrt{5}}{49}

x 0 = 177 5 50 x'_0 = \frac{177\sqrt{5}}{50}

y 0 = 179 5 100 y'_0 = \frac{179\sqrt{5}}{100}

This also means that:

x 0 = x 0 cos θ y 0 sin θ = 529 100 x_0 = x'_0 \cos \theta - y'_0 \sin \theta = \frac{529}{100}

y 0 = x 0 sin θ + y 0 cos θ = 178 25 y_0 = x'_0 \sin \theta + y'_0 \cos \theta = \frac{178}{25}

Therefore, a = 5 5 49 a = \frac{5\sqrt{5}}{49} , x 0 = 529 100 x_0 = \frac{529}{100} , y 0 = 178 25 y_0 = \frac{178}{25} , θ 0 = θ = cos 1 ( 2 5 5 ) \theta_0 = \theta = \cos^{-1} (\frac{2\sqrt{5}}{5}) , and a + x 0 + y 0 + θ 0 = 60809 + 500 5 4900 + cos 1 ( 2 5 5 ) 13.1 a + x_0 + y_0 + \theta_0 = \frac{60809 + 500\sqrt{5}}{4900} + \cos^{-1} (\frac{2\sqrt{5}}{5}) \approx \boxed{13.1} .

Hosam Hajjir
Jul 13, 2020

Substituting t = t + d t = t' + d , then

r ( t ) = C + f 1 ( t + d ) + f 2 ( t + d ) 2 \mathbf{r}(t') = \mathbf{C}+ \mathbf{f_1}(t' + d) + \mathbf{f_2} (t'+d)^2

= V + g 1 t + g 2 t 2 = \mathbf{V} + \mathbf{g_1} t' + \mathbf{g_2} t'^2

where V = C + f 1 d + f 2 d 2 \mathbf{V} = \mathbf{C} + \mathbf{f_1} d + \mathbf{f_2} d^2 , g 1 = f 1 + 2 d f 2 \mathbf{g_1} = \mathbf{f_1} + 2 d \mathbf{f_2} and g 2 = f 2 \mathbf{g_2} = \mathbf{f_2}

We want g 1 \mathbf{g_1} and g 2 \mathbf{g_2} to be perpendicular to each other, so that r \mathbf{r} can be expressed in terms of two mutually perpendicular vectors comprising a (rotated) coordinate frame.

Setting g 1 g 2 = 0 \mathbf{g_1} \cdot \mathbf{g_2} = 0 gives us ( f 1 + 2 d f 2 ) f 2 = 0 (\mathbf{f_1} + 2 d \mathbf{f_2}) \cdot \mathbf{f_2} = 0 , from which d = f 1 f 2 2 f 2 f 2 d = -\dfrac{ \mathbf{f_1} \cdot \mathbf{f_2} }{ 2 \mathbf{f_2} \cdot \mathbf{f_2} }

so that V \mathbf{V} , g 1 \mathbf{g_1} and g 2 \mathbf{g_2} are now fully specified.

Now let, u 1 = g 1 g 1 , u 2 = g 2 g 2 \mathbf{u_1} = \dfrac{ \mathbf{g_1} } { | \mathbf{g_1} | } , \mathbf{u_2} = \dfrac{ \mathbf{g_2} } { | \mathbf{g_2} | } , then

r ( t ) = V + g 1 t u 1 + g 2 t 2 u 2 \mathbf{r}(t') = \mathbf{V} + | \mathbf{g_1} | t' \mathbf{u_1} + | \mathbf{g_2} | t'^2 \mathbf{u_2}

Defining r = r V \mathbf{r'} = \mathbf{r} - \mathbf{V} , x = g 1 t x' = | \mathbf{g_1} | t' , y = g 2 t 2 y' =| \mathbf{g_2} | t'^2 , then

r = [ u 1 , u 2 ] [ x , y ] T \mathbf{r'} = [\mathbf{u_1}, \mathbf{u_2} ] [x', y']^T

Hence, ( x , y ) (x', y') are the coordinates of r r with respect to a frame having its origin at V \mathbf{V} , and whose x x' axis is along u 1 \mathbf{u_1} and y y' axis is along u 2 \mathbf{u_2} .

The relation between y y' and x x' can be found by eliminating the parameter t t' , and one finds that y = a x 2 y' = a x'^2 , where a = g 2 g 1 2 a = \dfrac{| \mathbf{g_2} |} { | \mathbf{g_1} |^2}

The angle θ 0 \theta_0 is just the angle between u 1 \mathbf{u_1} and the x-axis , so θ 0 = cos 1 ( u 1 x ) \theta_0 = \cos^{-1}( \mathbf{u_1}_x ) . The only thing to watch out for here is the case when u 2 \mathbf{u_2} is a rotation by 9 0 -90^{\circ} from u 1 \mathbf{u_1} (not + 9 0 +90^{\circ} as it should be for a right handed coordinate system). In this case, we reverse the direction of u 1 \mathbf{u_1} , so that u 1 = g 1 g 1 \mathbf{u_1} = - \dfrac{ \mathbf{g_1}}{ | \mathbf{g_1} |} . From the symmetry of the parabola this does not change the value of a a , but it does change θ 0 \theta_0 .

Using the values for the vectors as specified in the problem, one obtains a = 0.228170202 , V = ( 5.29 , 7.12 ) , θ 0 = 0.463647609 a = 0.228170202 , \mathbf{V} = (5.29,7.12) , \theta_0 = 0.463647609 , and this makes the answer 13.1 \boxed{13.1}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...